2016
DOI: 10.5320/wjr.v6.i3.69
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary complications of transcatheter arterial chemoembolization for hepatocellular carcinoma

Abstract: Transarterial chemoembolization (TACE) is an effective palliative intervention that is widely accepted for the management of hepatocellular carcinoma (HCC). Post-TACE pulmonary complications resulting in acute lung injury (ALI) or acute respiratory distress syndrome (ARDS) are rare events. Pulmonary complications after TACE are thought to be related to chemical injury subsequent to the migration of the infused ethiodized oil or chemotherapeutic agent to the lung vasculature, facilitated by arteriovenous (AV) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…Iezzi et al[ 29 ] reported that for patients with HCC > 3 cm, the long-term survival of RFA combined with TACE was better than that of TACE or RFA alone. It is worth noting that the traditional emulsion has poor stability, and the chemotherapeutic drugs are easily diffused into the patient's peripheral circulatory system, resulting in an uncontrolled local release of the drug, and easily reducing the local treatment effect and aggravating the systemic adverse reactions of the chemotherapeutic drugs[ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Iezzi et al[ 29 ] reported that for patients with HCC > 3 cm, the long-term survival of RFA combined with TACE was better than that of TACE or RFA alone. It is worth noting that the traditional emulsion has poor stability, and the chemotherapeutic drugs are easily diffused into the patient's peripheral circulatory system, resulting in an uncontrolled local release of the drug, and easily reducing the local treatment effect and aggravating the systemic adverse reactions of the chemotherapeutic drugs[ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary embolism (PE) is a blockage of an artery in the lungs by a substance that has travelled from elsewhere in the body through the bloodstream,1 which results in between 50 000 and 200 000 deaths in United States every year 2…”
Section: Tablementioning
confidence: 99%
“…cTACE is applied in clinical practice with a longer period than DEB-TACE, thus articles focusing on the TACE of EHC blood supplies are limited to cTACE. [12][13][14][15] In the other words, the role of DEB-TACE in the treatment of EHC blood supplies of HCC is still undetermined.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, no grade 3-4 liver toxicity was documented in all patients in our study, indicating that TACE of EHC arteries is safe with regard to liver function. The safety of transarterial management for HCC with the IPA has been evaluated in several studies, [12][13][14][15] and most of the adverse events were pulmonary complications, of which fewer than 5% met the definition for major complications. 13 In our study, DEB-TACE and cTACE showed no significant difference in both major and minor complications.…”
mentioning
confidence: 99%
See 1 more Smart Citation